Cerebral blood flow and oximetry response to blood transfusion in relation to chronological age in preterm infants. (June 2016) - Banerjee, J.; Leung, T.S.; Aladangady, N.
Abstract: Objective: Preterm infants frequently receive blood transfusion (BT) and the aim of this study was to measure the effect of BT on cerebral blood flow and oxygenation in preterm infants in relation to chronological age. Patients: Preterm infants undergoing intensive care recruited to three chronological age groups: 1 to 7 (Group 1; n = 20), 8 to 28 (Group 2; n = 21) & ≥ 29 days of life (Group 3; n = 18). Methods: Pre and post-BT anterior cerebral artery (ACA) time averaged mean velocity (TAMV) and superior vena cava (SVC) flow were measured. Cerebral Tissue Haemoglobin Index (cTHI) and Oxygenation Index (cTOI) were measured from 15–20 min before to 15–20 min post-BT using NIRS. Vital parameters and blood pressure were measured continuously. Results: Mean BP increased significantly, and there was no significant change in vital parameters following BT. Pre-BT ACA TAMV was higher in Group 2 and 3 compared to Group 1 (p < 0.001). Pre-BT ACA TAMV decreased significantly (p ≤ 0.04) in all 3 groups; pre-BT SVC flow decreased significantly in Group 1 (p = 0.03) and Group 3 (p < 0.001) following BT. Pre-BT cTOI was significantly lower in Group 3 compared to Group 1 (p = 0.02). cTHI (p < 0.001) and cTOI (p < 0.05) increased significantly post-BT in all three groups. PDA had no effect on these measurements. Conclusion: Baseline cTOI decreases and ACA TAMV increases with increasing chronological age. Blood transfusion increased cTOI and cTHI and decreased ACA TAMV in all groups. PDA had no impact on the baseline cerebral oximetry and blood flow as well as changes following blood transfusion. Highlights: Preterm receive frequent blood transfusions but its effect on cerebral perfusion at various chronological ages is not studied. This study demonstrates the effect of blood transfusion on cerebral perfusion at various chronological age groups in preterm.